Geomaterials and decay forms of the coastal towers of Piscinni and Foghe, Weastern Sardinia - Carcangiu, Gianfranco (2022)
The distribution of Coastal Towers in Sardinia testify that foreign invasions, which occurred several times over the centuries, were particularly frequent and dangerous. The beginning of the eighth century signed an increase of the attacks from the sea. The most of Coastal Towers were built in the period of Spanish rule, from 1583 to 1720. Despite numerous restorations over the years, many of these defensive structures are in critical conditions, some also affected by structural collapse. The building materials are closely related to local geological outcrops, and consist of sedimentary, magmatic and metamorphic rocks. Study of different lithotypes allowed assessing the vulnerability of different materials in different environmental conditions. Salts, transported by aerosols and deposited inside the porous structures, are the principal cause of decay of the building materials. Chemical-physical and mineralogical-petrographic analyses, performed on some Towers allowed making some general assessments on their conservation status and restoration projects.